Considerações sobre a deformação permanente de pavimentos asfálticos no dimensionamento mecanístico-empírico - Bastos, Juceline Batista dos Santos (2017)
Rutting is a common distress in Brazilian asphalt pavements. It contributes to reduce the driving comfort and safety, and increases operational costs. The present Ph.D. dissertation ads to the new Brazilian Mechanistic-Empirical Pavement Design method under development with respect to aspects related to permanent deformation of asphalt mixtures used in surface courses. The methodologies to assess the evolution of the referred distress based on laboratory results from the Triaxial Stress Sweep (TSS) and the uniaxial repeated load tests are investigated. Field measurements over time are also considered. The rutting of 03 monitored real sections and 02 sections built for this research and submitted to the Heavy Vehicle Simulator (HVS) were monitored, with a reference section properly instrumented. In addition to field monitoring, the behavior of the respective materials was determined in the laboratory. Field and laboratory results indicated the need to adapt the TSS protocol to the conditions of Brazilian pavements. With such adaptation, rutting predictions were consistent with the field performance. It was therefore possible to calibrate the performance curves from the TSS test results, in addition to the validation of the evolution models for the investigated failure. Moreover, the Flow Number (FN) criteria used in the uniaxial repeated load test were refined as a function of traffic. In the laboratory, the investigation extended through the asphalt binders, by Multiple Stress Creep and Recovery (MSCR), and the aggregates, both with respect to particle size (gradation), through the Dominant Aggregate Size Range (DASR) model and the Bailey method, and with respect to form, by means of the Aggregate Image Measurement System 2 (AIMS 2). A strong correlation was found between the components of the asphalt mixtures [the proportion of Coarse Aggregates (CA) (Bailey) and the parameter form 2D from AIMS 2] with the FN; besides the contribution of the binder in the resistance to permanent deformation. In the field, the instrumentation and the monitoring of the test sections submitted to the HVS load applications allowed a better understanding of the in situ the behavior of a typical asphalt pavement in the state of Ceará.